Comparison of Traditional Chinese Exercises and Nontraditional Chinese Exercise Modalities on Cognitive and Executive Function in Community Middle-Aged and Older Adults: A Cross-Sectional Study. (23rd November 2020) - Ye, Mingzhu; Xiong, Jian; Zhao, Fang; Sun, Shanshan; Wang, Lecong; Zheng, Guohua
Abstract : Background . Current evidence indicates that regular exercise can have a positive impact on cognitive function in older adults, but whether different exercise modalities may induce differential protective effects in different cognitive domains is uncertain. Objective . To compare the effect of traditional Chinese exercise (TCE) modalities and non-traditional Chinese exercise (non-TCE) modalities on cognitive and executive function in community middle-aged and older adults through a cross-sectional study. Methods . A total of 350 community middle-aged and older adults aged over 55 years participated in this study. Information on demographic characteristics, lifestyle and behavioural habits, and regular exercise was collected by a self-designed questionnaire. Global cognitive ability and executive function were assessed using the Montreal Cognitive Assessment (MoCA) scale, the clock drawing test (CDT), the animal naming test (ANT), and the trail making test (TMT). Eligible subjects were categorized into the no regular exercise (no-RE), non-TCE, or TCE groups according to their self-reported exercise information. Comparisons of global cognitive and executive function among the three groups were conducted using ANOVA or the general linear model with adjustment for potential confounding factors. Results . The results showed that for the non-TCE or TCE groups, the MoCA and CDT scores were significantly higher, and the TMT-A test time was significantly shorter than those in the no-RE group (all P < 0.05 ), but no significant difference was observed for the TMT-B and ANT tests. After adjustment for potential confounding factors, the MoCA, the CDT, and TMT-A scores in the TCE group were significant compared to those in the no-RE group. In addition, subgroup analysis showed that in the TCE group, the MoCA scores were significantly higher than those in the non-TCE group. Furthermore, in the TCE group, the CDT scores for those with an exercise duration of <5 years were higher and the TMT-A test time for those with an exercise duration of ≥5 years was shorter than those in the non-TCE group. Conclusions . Both TCE and non-TCE have potential protective effects on global cognitive and executive function in community middle-aged and older adults. Compared to the non-TCE modality, the TCE modality may have a more positive association with these protective effects. Furthermore, prospective studies are needed to confirm these findings.